ANTHROPOMORPHISM IN THE TALE OF BAYAN BUDIMAN - SYAM, ESSY; ARIS, QORI ISLAMI; SARI, YESSI RATNA (Universitas Negeri Medan, 2024)
This research analyzes the element of anthropomorphism in the classical Malay literary work entitled